The Influence of Product Quality and Promotion on Purchase Decisions of Seasoned Flour in Modern Markets: Study On One Of The Food Companies In Bandung - Erwin Setiawan; Anton Tirta Komara; Asep Rochyadi Suherman; Ashila Dwiyanisa (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2025)
This study seeks to determine the substantial influence of product quality and advertising on consumer purchasing decisions.  The research analyzed users of seasoned flour in the current market, employing data from questionnaires distributed to chosen participants.  The research employed a sample-based methodology to elucidate consumer purchase behavior.  The research classified variables as independent and dependent types.  The independent variables were product quality and promotion, whereas the dependent variable was the purchase decision.  The research process necessitated an evaluation of the validity and reliability of the instruments employed, which was succeeded by data analysis via route analysis utilizing the SPSS application.  The findings indicated that product quality and advertising significantly influenced consumer purchasing decisions.  The results indicate that product quality affects purchase decisions, highlighting its importance in influencing client preferences.  Conversely, promotion exerts a more substantial impact, underscoring the necessity for effective marketing strategies to attract and keep customers.  The coefficient of determination analysis revealed that product quality and promotion substantially affect purchase decisions.  Nonetheless, unexamined factors also affect customer decisions.  Management should prioritize preserving and enhancing product quality and promotional activities to sustain consumer engagement and improve purchasing decisions.  Ensuring consistent product quality cultivates customer trust and loyalty, whereas efficient promotional strategies enhance brand visibility and attract new clients.  This study emphasizes integrating quality enhancement and marketing strategies to attain a competitive edge in the current market landscape.  Future research may explore additional elements that affect purchasing decisions to enhance comprehension of customer behavior in the food industry.